A new method for assessment of the sludge disintegration degree with the use of differential centrifugal sedimentation - Silvestri, Daniele; Wacławek, Stanisław; Gončuková, Zuzanna; Padil, Vinod V T; Grübel, Klaudiusz; Černík, Miroslav (Environmental technology, 2019)
A novel method for assessing the disintegration degree (DD) of waste activated sludge (WAS) with the use of differential centrifugal sedimentation method (DCS) was shown herein. The method was validated for a WAS sample at four levels of disintegration in the range of 14.4-82.6% corresponding to the median particle size range of 8.5-1.6 µm. From the several sludge disintegration methods used (i.e. microwave, alkalization, ultrasounds and peroxydisulfate activated by ultrasounds), the activated peroxydisulfate disintegration resulted in the greatest DD 83% and the smallest median particle size of WAS. Particle size distribution of pretreated sludge, measured by DCS, was in a negative correlation with the DD, determined from soluble chemical oxygen demand (SCOD; determination coefficient of 0.995). Based on the obtained results, it may be concluded that the DCS analysis can approximate the WAS disintegration degree.
Keywords: WAS disintegration; disintegration degree; Waste Disposal, Fluid; odpad tekutý - odstraňování; chemical oxygen demand; měření biologické spotřeby kyslíku; sludge particle size; differential centrifugal sedimentation; odpadní vody; Particle Size; Sewage; mikrovlny; Biological Oxygen Demand Analysis; Microwaves; velikost částic